Effectiveness of Personal versus Online Extension Methods in Disseminating Knowledge on Household Waste Management (Indian Journal of Extension Education, 2022)
The article highlights the effectiveness of personal and online extension methods for disseminating knowledge on household waste management. A pre-test, post-test experimental design was used for the study. Thirty women, each from five randomly selected urban localities of Ludhiana district of Punjab were selected for the study, making a total of 150 respondents as the sample size. Of the five urban localities, four localities were randomly chosen for the experiment and one locality was chosen as the control group. Data was collected using a structured interview schedule consisting of a self-designed knowledge test on household waste management. Findings revealed that all the selected extension methods were effective in disseminating knowledge to the respondents. The most effective extension method was personal contact + print material followed by video conferencing + ICT based messages, video conferencing, and personal contact method. One way ANOVA revealed significant differences in gain in knowledge by the respondents of the study groups’ p < 0.001. Post-hoc analysis further revealed that the effect of both personal and online extension methods when supplemented with educational materials and when used solo, had statistically similar effects on gain in knowledge.